The Impact of Risk-Based ESG Scores, Return on Asset (ROA) and Return on Equity (ROE) on Firm Value - Rahmania, Thriyani; Ermawati, Wita Juwita; Suprayitno, Gendut (Institut Pertanian Bogor, 2025)
The urgency to understand the impact of risk-based Environmental, Social, and Governance (ESG) and financial factors on firm value remains high, especially for listed companies in Indonesia. Indonesia is a disaster-prone country. World Risk Report in 2021 shows that Indonesia ranks 38th out of 181 countries in the